2002
DOI: 10.1128/aem.68.10.4863-4870.2002
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of 2-Benzoxazolinone and 2-Hydroxy-1,4-Benzoxazin-3-one by Endophytic Fungi Isolated from Aphelandra tetragona

Abstract: The biotransformation of the phytoanticipins 2-benzoxazolinone (BOA) and 2-hydroxy-1,4-benzoxazin-3-one (HBOA) by four endophytic fungi isolated from Aphelandra tetragona was studied. Using high-performance liquid chromatography-mass spectrometry, several new products of acylation, oxidation, reduction, hydrolysis, and nitration were identified. Fusarium sambucinum detoxified BOA and HBOA to N-(2-hydroxyphenyl)malonamic acid. Plectosporium tabacinum, Gliocladium cibotii, and Chaetosphaeria sp. transformed HBOA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
117
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(127 citation statements)
references
References 19 publications
9
117
0
1
Order By: Relevance
“…Several authors reported their presence in other systems in which these degradations take place (16,17). Their N-acetyl derivatives, 2-acetamidophenoxazin-3-one (AAPO) and 2-acetamido-7-methoxyphenoxazin-3-one (AAMPO) (Table 2, B), have been proposed as detoxification compounds produced by nonpathogenic organisms associated to Gramineae (15,18). APO has been already described as a potent phytotoxic agent for Echinochloa crus-galli (barnyardgrass) (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors reported their presence in other systems in which these degradations take place (16,17). Their N-acetyl derivatives, 2-acetamidophenoxazin-3-one (AAPO) and 2-acetamido-7-methoxyphenoxazin-3-one (AAMPO) (Table 2, B), have been proposed as detoxification compounds produced by nonpathogenic organisms associated to Gramineae (15,18). APO has been already described as a potent phytotoxic agent for Echinochloa crus-galli (barnyardgrass) (16).…”
Section: Introductionmentioning
confidence: 99%
“…In general terms, natural 2,4-dihydroxybenzoxazin-3-ones (DIMBOA, DIBOA) ( In addition to this bioactivity research, the low stability of DIMBOA, DIBOA, and their related benzoxazolinones in several conditions, such as biotransformation by fungi (15), and degradation in crop soil (16,17) and in aqueous solution (8)(9)(10), has been investigated. We have recently developed a complete degradation study of these allelochemicals in wheat crop soil in which we observed and characterized the conversion dynamics of these compounds into several molecules carried out by soil microbial population (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Another maize pathogen, Gaumannomyces graminis var. tritici, transformed BOA to APO in liquid culture (Friebe et al 1998), and APO is now known to occur in cultures of several root endophytic fungi of tobacco, including F. sambucinum (Zikmundova et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…This ascomycetous fungus is consistently found in association with maize throughout the world as a symptomless endophyte (Kommedahl and Windels 1981;Marasas et al 1984;Bacon and Hinton 1996). The symptomless endophytic association with maize is apparently evolutionarily relevant, as it has been established that F. verticillioides and other endophytic fungi detoxify DIMBOA/MBOA and DIBOA/BOA by actively transforming them into the nontoxic components N-(2-hydroxy-4-methoxyphenyl) malonamic acid (HMPMA) and N-(2-hydroxyphenyl) malonamic acid (HPMA), respectively (Virtanen and Hietala 1955;Zikmundova et al 2002;Glenn et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…26 Endophytes have also been successfully used in the biotransformation of natural products. 27,28 These findings stimulated us to investigate about 20 endophytic strains from our collection of fungi 29 as biocatalyst systems and effective method for regio-and stereoselective production of novel and bioactive products. This procedure could convert unreactive methoxy groups to hydroxyl functions of a tetrahydrofuran lignan under mild conditions which may increase the solubility of 6.…”
Section: Introductionmentioning
confidence: 99%